2005
DOI: 10.1128/jb.187.3.862-871.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate:Quinone Oxidoreductase from Corynebacterium glutamicum : Purification and Biochemical Characterization

Abstract: Pyruvate:quinone oxidoreductase catalyzes the oxidative decarboxylation of pyruvate to acetate and CO 2 with a quinone as the physiological electron acceptor. So far, this enzyme activity has been found only in Escherichia coli. Using 2,6-dichloroindophenol as an artificial electron acceptor, we detected pyruvate:quinone oxidoreductase activity in cell extracts of the amino acid producer Corynebacterium glutamicum. The activity was highest (0.055 ؎ 0.005 U/mg of protein) in cells grown on complex medium and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 72 publications
3
39
0
Order By: Relevance
“…Like the E. coli enzyme, the C. glutamicum PQO is a homotetrameric flavoprotein containing TPP, and it is activated by Triton X-100, phosphatidylglycerol and dipalmitoyl-phosphatidylglycerol. In contrast, it does not reduce ferricyanide, which is routinely used for assaying the E. coli enzyme (1,9,75), and it probably uses a menaquinone instead of ubiquinone as the physiological electron acceptor (59). The C. glutamicum PQO activity was highest in cells grown on complex medium and about threefold lower when glucose was added to the complex medium or when the cells were grown on minimal medium containing different carbon sources, suggesting that the enzyme is regulated by the carbon source in the growth medium.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Like the E. coli enzyme, the C. glutamicum PQO is a homotetrameric flavoprotein containing TPP, and it is activated by Triton X-100, phosphatidylglycerol and dipalmitoyl-phosphatidylglycerol. In contrast, it does not reduce ferricyanide, which is routinely used for assaying the E. coli enzyme (1,9,75), and it probably uses a menaquinone instead of ubiquinone as the physiological electron acceptor (59). The C. glutamicum PQO activity was highest in cells grown on complex medium and about threefold lower when glucose was added to the complex medium or when the cells were grown on minimal medium containing different carbon sources, suggesting that the enzyme is regulated by the carbon source in the growth medium.…”
mentioning
confidence: 99%
“…Very recently, we showed for the first time the presence of PQO activity in a prokaryotic organism apart from E. coli and described the isolation, purification, and biochemical analysis of the PQO enzyme from Corynebacterium glutamicum (59). This bacterium is an aerobic, "high-GC gram-positive" organism that grows on a variety of sugars and organic acids and is widely used in the industrial production of amino acids, particularly L-glutamate and L-lysine (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent phylogenetic survey of PQO type (e.g., EcPOX) and POX type (e.g., LpPOX) enzymes, it appears that they are interspersed in gram positive and gram negative bacteria lineages (62). In the same study, physiological experiments with Corynebacterium glutamicum, a gram-positive aerobe expressing a PQO type enzyme, suggested that this enzyme is regulated by carbon sources rather than growth phase as observed for EcPOX (61,62). The authors concluded that the difference in the surrounding genetic makeup of the C. glutamicum pqo gene compared to the poxB gene in E. coli were most likely responsible for the regulational differences (61,62).…”
Section: Nifl (Transcriptional Regulator Of Nitrogen Fixation)mentioning
confidence: 77%
“…In the same study, physiological experiments with Corynebacterium glutamicum, a gram-positive aerobe expressing a PQO type enzyme, suggested that this enzyme is regulated by carbon sources rather than growth phase as observed for EcPOX (61,62). The authors concluded that the difference in the surrounding genetic makeup of the C. glutamicum pqo gene compared to the poxB gene in E. coli were most likely responsible for the regulational differences (61,62). With a paucity of literature on PQO type enzymes from organisms other than E. coli, the remainder of this section will focus on EcPOX.…”
Section: Nifl (Transcriptional Regulator Of Nitrogen Fixation)mentioning
confidence: 94%